2022
DOI: 10.1007/s11426-022-1253-7
|View full text |Cite
|
Sign up to set email alerts
|

Turning weak into strong: on the CTAB-induced active surface growth

Abstract: Discovering new methods and principles in the inequivalent growth of equivalent facets is of great significance for going beyond symmetrical nanocrystals and for out-of-box exploration. In this work, we demonstrate that a middle ground exists between the traditional weak ligands and the strong ligands with unusual growth modes. By modifying the seed concentration during the growth of pentagonal Au nanorods, the typical weak ligand cetyltrimethylammonium bromide (CTAB) is made strong, leading to notches of rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 33 publications
2
22
0
Order By: Relevance
“…Previously, we have shown 3 stages of the CTAB-induced ASG on decahedron seeds, 17 with additional curvature effects: (1) when the rate of Au deposition is low (not choked condition, or the normal facet control), the growth mode is the uniform expansion of all facets, similar to the observations in Fig. 4b.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Previously, we have shown 3 stages of the CTAB-induced ASG on decahedron seeds, 17 with additional curvature effects: (1) when the rate of Au deposition is low (not choked condition, or the normal facet control), the growth mode is the uniform expansion of all facets, similar to the observations in Fig. 4b.…”
Section: Resultssupporting
confidence: 81%
“…According to our previous hypothesis, the rate of Au deposition has probably exceeded the limit (the choked condition) allowed by the association-dissociation dynamics of CTAB. 17 As illustrated in Fig. 1b, the excess Au is diverted to a few active sites (tips and ridges), where the freshly grown surface has even fewer ligands, further promoting the growth.…”
Section: Resultsmentioning
confidence: 96%
“…Despite the first impression of regular angles and flat flakes, the presence of distorted ridge lines, wavy surfaces, and curved edges suggests that the growth is not governed by the conventional facet control. [9,21] In comparison to the initial Au nanoplates with edge length of 150 nm and thickness of 8 nm, [22] the edge of the nano-badges increased dramatically to 450-570 nm and the thickness to 140-230 nm, judging from the occasional nano-badges that stand on their sides (Figure S1, Supporting Information). The products have triangular or hexagonal outline, suggesting that they are derived from the nanoplate seeds.…”
Section: Resultsmentioning
confidence: 98%
“…Basically, we found that there is a limit in the rate of deposition allowed by the ligand dynamics (strong ligands typically have slow dynamics). [ 9 ] When the deposition rate exceeds the limit, the excess growth materials are diverted to a few active sites giving spikes. As the freshly grown surface has intrinsically fewer ligands and thus faster ligand dynamics, a divergent growth mode ensues such that the fresh surface becomes fresher and the old surface older.…”
Section: Introductionmentioning
confidence: 99%
“…In our model study using Au decahedrons as seeds and CTAB as the only ligand, we came to realize that the active surface growth is not black-and-white with drastic difference between the active sites and totally inhibited surfaces. The critical factor is the relative activity, which depends on the growth conditions.…”
Section: Active Surface Growthmentioning
confidence: 99%